Critical successful factors for innovation in Vietnamese firms - Tran Hoai Nam; Nham Phong Tuan; Nguyen Van Minh (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: Innovation is considered as a core element of sustainable competitive advantage in the rapidly changing environment. However, in Vietnam, researches on innovation are very rare, which are mostly general reports without underlying analyses of innovation in firms, especially determinants for innovation. Therefore, this paper focuses on analyzing critical successful factors for innovation in Vietnamese firms. Design/methodology/approach: This study used primary data through questionnaire survey from November 2015 to February 2016. Respondents were senior managers of firms located mostly at Hanoi (Northern), Hochiminh (Southern) and Danang city (Central). The questionnaire included multi-items designed to measure factors. Each item was measured by 5 point Likert scale: 1 (strongly disagree) to 5 (strongly agree). Questionnaires were administerd to 500 firms belonging to list of Vietnam Chamber of Commerce and Industry (VCCI) in these three cities with rate of 40% (Hochiminh city), 40% (Hanoi city) and Danang (20%). However, there were 360 returned questionnaires and valid to next analyses. Analysis methodologies of reliability, factor analysis and regression are utilized in this paper. Findings: We developed and tested a model of determinants for Innovation in Vietnamese firms. The major contribution of this study is testing six determinants for innovation in Vietnamese companies. The results showed that awareness of innovation, innovation strategy and policy, organization for innovation, HR for innovation and building capabilities have positive impact on innovation. Originality/value: This study makes a contribution for both academics and practitioners. For academics, this study provided one more empirical evidence of the determinants for innovation. Regarding practical implications, this study suggests that Vietnamese companies have to strengthen capabilities for employees through training, encourage generation of new ideas, rule breaking, and innovative behaviors by organizational members. Together, having high awareness of innovation, building rational innovation strategy and policy is essential factors that firms should possess and develop to enhance innovation performance. Although there is no confirmation for impact of finance on innovation level, firms should understand that increasing innovation investment can bring favorable condition to create innovation especially in SMEs.
Keywords: 650; innovation; critical successful factors; Vietnam